Hubungan Antara Kepatuhan Berobat dengan Keberhasilan Pengobatan Pasien Tuberkulosis Paru di Rsud Al–Ihsan Tahun 2021 - Chirgo Rahmat Basdiwo; Wida Purbaningsih; Susan Fitriyana (Bandung Conference Series: Medical Science, 2022)
Abstract. Tuberculosis cases in West Java increase every year, namely in 2017 there were 82,063 cases and in 2016 there were 72,558 cases, so there was an increase of 13.16% when compared between 2017 and 2016. In West Java, there are three districts with the highest TB incidence. , including Bandung Regency, Bogor Regency and Bandung City with 9-12% of the number of new cases in West Java. The purpose of this study was to determine the relationship between medication adherence and treatment success in pulmonary TB patients at AL-IHSAN Hospital. This research is an analytic observational with a cross sectional design. The subjects of this study were pulmonary TB patients who met the inclusion criteria and exclusion criteria. Data were obtained from medical records for the 2020-2021 period with 100 subjects. The results of the study showed that the number of patients who adhered to treatment was 59 people (73.75%) and those who recovered were 77 people (96.25%). Based on the frequency distribution, the highest number of male sex was 57.5% (46 people) and aged 0-5 years, namely 34 children (42.5). The results of bivariate analysis with chi square test showed that there was a relationship between medication adherence and treatment success. pulmonary tuberculosis patients. The older the patient, the more positive his attitude towards pulmonary TB treatment will be. Pulmonary TB patients aged 40-60 years showed a positive attitude towards pulmonary TB treatment, while at a young age they showed more negative attitudes and could have bad consequences. Abstrak. Kasus TB di jawa barat semakin meningkat dari tahun ke tahun. Salah satu yang masih menjadi masalah dari TB adalah rendahnya keberhasilan pengobatan TB. Tujuan dari penelitian ini adalah untuk mengetahui hubungan antara kepatuhan berobat dengan keberhasilan pengobatan pada pasien TB Paru di RSUD Al-Ihsan. Penelitian ini merupakan penelitian observasional analitik dengan desain cross sectional. Subjek penelitian ini adalah pasien TB paru yang memenuhi kriteria inklusi dan kriteria eksklusi serta pengambilan data menggunakan data sekunder Data diperoleh dari rekam medis pada periode 2020-2021dengan jumlah subjek 100 orang. Hasil penelitan dari uisa pasien yang banyak terdapat TB Paru yaitu usia 0 – 5 tahun yaitu sebanyak 34 orang (43%) dan berjenis kelamin laki – laki yaitu sebanyak 46 orang (58%), Jumlah pasien patuh berobat sebanyak 59 orang (73,75%) dan yang sembuh sebanyak 77 orang (96,25%). Berdasarkan distribusi frekuensi maka didapat jumlah tertinggi jenis kelamin laki laki sebanyak 57,5% (46 orang) dan usia 2 - 10 tahun yaitu 40 anak (50%). Hasil analisis bivariat dengan uji chi square menunjukkan adanya hubungan kepatuhan berobat dengan keberhasilan pengobatan pasien tuberkulosis. Semakin patuh pasien dalam pengobatan, maka semakin tingkat kesembuhan pada Tb Paru semakin tinggi.